Aplication of Natural Fermantation To Ferment Mulberry Juice Into Alcoholic Beverage - Duyen, Nguyen Thi; Hai, Le Thanh; Minh, Nguyen Phuoc; Anh Dao, Dong Thi (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
Mulberry (Morus nigra) is a fruit not known only for its nutritional qualities and its flavour, but also for its traditional use in natural medicine as it has a high content of active therapeutic compounds. Mulberries are considered as valuable materials for pharmaceutical use because of bioactive compounds. In order to find the optimal conditions for the fermentation process, the juice is fermented naturally in various conditions to get its alcoholic beverage. The results are as follows: initial mulberry juice with 24oBx and pH 3.5, fermentation temperature 18Ã·20oC. Fermentation is carried out for 96h and the ethanol content of product was 5 %v/v. This product is suitable for Vietnam customers. This process can be applied to industrial scale.